Resistência à corrosão e ao desgaste de recobrimentos metálicos produzidos com ligas amorfizáveis a base de ferro - Berger, José Eduardo (2014)
Amorphous Iron-based alloys can be processed in such a way that, if well designed, it can ensure an attractive combination of mechanical and electrochemical properties, particularly in petrochemical industries where high level of wear and corrosion resistance is required. The success in obtaining such properties is dependent on the design quality, which is dependent on the level of technical-scientific knowledge of the area. Thus, in the present work, we attempted to conciliate a scientific study and a practical application. The work was divided into three parts, the first one is: the evaluation of corrosion resistance of amorphous alloys in the form of ribbons prepared by melt spinning from pure elements; the second one is: the characterization and evaluation of electrochemical properties of amorphous ribbons made of superduplex commercial alloy modified with boron (SDM) in front of the crystallization level. And, in the last part, a more practical application was developed, where in partnership with Hydro-Québec in Canada, the HVOF thermal spray process in substrate pipes used in drilling wells by Petrobrás Company was performed. Powders from spray forming and high energy ball milling as ZOZ mill type were produced, the coatings showed different levels of crystallization. In this way it was possible to conciliate the results with those obtained from previous steps. The characterizations were performed by several techniques such as XRD, DSC, SEM, TEM, EDS, MO, analysis of hardness and porosity. The corrosion resistance properties were evaluated from the polarization curves for high salt media (35 g/L NaCl) and the coatings were evaluated by abrasive wear tests on dry sand/rubber wheel. The results indicated a large capacity of alloy SDM to achieve a combination of properties such as corrosion and wear resistance.